Identity unknown eaudiobook - Cornwell, Patricia (Kay Scarpetta, 2024)
From a bestselling author, a "hauntingly original, impossibly clever and devilishly daring" thriller in which Scarpetta receives a message from beyond the grave...(Chris Whitaker, author of All the Colors of the Dark ) Autopsies can reveal the secrets of the dead. And this victim is sending Scarpetta a message... Summoned to an abandoned theme park to retrieve a body, Dr. Kay Scarpetta is devastated to learn that the victim is a man she once had an intense love affair with. The murder scene is bizarre, with a crop circle of petals around the body, and Giordano's skin is strangely red. Scarpetta's niece Lucy believes he was dropped from an unidentified flying craft. Scarpetta knows an autopsy can reveal the dead's secrets, but she is shocked to find her friend seems to have deliberately left her a clue. As the investigators are torn between suspicions of otherworldly forces, and of Giordano himself, Scarpetta detects an explanation closer to home that, in her mind, is far more evil...